Retinal Vessel Oxygen Saturation and Vessel Diameter in Inactive Graves Ophthalmopathy. Issue 6 (November 2017) - Yang, Xiaonan; Huang, Danping; Ai, Siming; Liang, Xuanwei; Zhao, Jing; Fang, Lei
Abstract : Purpose: To investigate whether inactive thyroid-associated ophthalmopathy (TAO) affects retinal oxygen saturation and/or vessel diameter. Methods: Via an observational case–control study, retinal circulation was measured in patients with inactive TAO (mild, moderate, and severe) and normal subjects by retinal oximetry. Complete ophthalmologic examination, including noncontact tonometry and Hertel exophthalmometry, was performed; history of smoking and dysthyroid disease were recorded. Analysis of variance or the Kruskal–Wallis test was used to compare oximetry values between TAO and controls. Simple linear regression was used to analyze the correlation of Hertel, smoking, and intraocular pressure with oximetry values. Results: Seventy-six eyes were enrolled: 19 controls, and 17 mild, 21 moderate, and 19 severe inactive TAO. Retinal oxygen saturation did not change significantly in inactive TAO versus controls; arteriole saturation: severe, 95.7% ± 7.0%; moderate, 93.2% ± 3.9%; mild, 90.3% ± 4.8%; and controls, 93.1% ± 6.4%; vein saturation: severe, 57.4% ± 7.1%; moderate, 59.0% ± 7.0, ; mild, 56.3% ± 7.9%; and controls, 58.5% ± 6.5%; arteriovenous saturation: severe, 38.3% ± 8.0%; moderate, 34.2% ± 7.1%; mild, 33.9% ± 6.8%; and controls, 34.6% ± 5.9%. However, retinal venous diameter with severe TAO (137.3 ± 12.5 μm) significantly decreased in comparison with controls (148.8 ± 10.2 μm, p = 0.017). Otherwise, no significant change in vessel diameter was found between TAO and controls. No statistically significant correlations were found between Hertel values or intraocular pressure and oximetry values. However, there was a positive significant correlation between smoking and arteriovenous oxygen saturation ( p = 0.017, β = 4.61). Conclusions: In inactive TAO versus controls, retinal oxygen saturation fluctuated and could be affected by smoking; however, the retinal venous diameter only decreased significantly for severe TAO. This implies that TAO may affect retinal circulation; this effect could be accelerated by smoking. Abstract : The retinal circulation of inactive Graves ophthalmopathy might be affected, and this effect could be accelerated by smoking.